Reframing Human Competence in the Digital Transformation Era: A Qualitative Study of Adaptive HR Practices. - Atmanegara, Ajeng; Aedy, Hasan; Hakim, Abdul (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The acceleration of digital transformation has fundamentally reshaped the paradigm of human competence, shifting from a focus on technical proficiency to adaptive and continuously evolving capabilities. This study aims to explore how adaptive human resource management (HRM) practices shape and strengthen human competence amid technological disruption. A qualitative phenomenological approach was employed, involving 15 key informants—including HR division heads, managers, employees, and HR consultants—from three organizational sectors: public administration, higher education, and financial services. Data were collected through in-depth interviews, participatory observation, and document analysis, and analyzed using thematic analysis supported by NVivo 14 software. The findings reveal four core dimensions of adaptive competence in the digital era: digital literacy, cognitive flexibility, collaborative intelligence, and transformative mindset. These dimensions collectively form the Adaptive Human Competence Framework (AHCF), which illustrates the dynamic interplay among individuals, organizations, and technology. The study further highlights that adaptive HR practices—such as learning ecosystems, digital mentoring, and agile performance management—serve as strategic catalysts for fostering trust-based and innovation-driven organizational cultures. Theoretically, this study extends the concept of competence-based HRM by integrating dynamic capabilities and adaptive learning theory. Practically, the findings emphasize the importance of developing collaborative, flexible, and human-centered digital learning ecosystems to ensure sustainable organizational performance in the digital transformation era.